1965
DOI: 10.1128/jb.90.1.29-37.1965
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Growth, Synthesis, and Permeability in Neurospora crassa by Phenethyl Alcohol

Abstract: Inhibition of the growth of Neurospora crassa in still culture was detected at 0.05% and was complete at a level of 0.2% phenethyl alcohol (PEA). Benzyl alcohol was less inhibitory, and 3-phenyl-1-propanol and phenol were more inhibitory, than PEA; benzylamine and phenethylamine were less inhibitory than the analogous hydroxylated compounds. Inhibition by PEA was not reversed by synthetic mixtures of purines and pyrimidines or vitamins, or by casein digests, yeast extract, or nutrient broth. The germination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

1967
1967
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(33 citation statements)
references
References 23 publications
(22 reference statements)
0
33
0
Order By: Relevance
“…Lester (14) showed that PEA alters the permeability to some amino acids in Neurospora crassa, and Silver and Wendt (27) also observed that PEA, like toluene (8), causes a breakdown of the permeability barrier to AF and potassium in E.…”
Section: Discussionmentioning
confidence: 99%
“…Lester (14) showed that PEA alters the permeability to some amino acids in Neurospora crassa, and Silver and Wendt (27) also observed that PEA, like toluene (8), causes a breakdown of the permeability barrier to AF and potassium in E.…”
Section: Discussionmentioning
confidence: 99%
“…Both aliphatic and aromatic alcohols are known inhibitors of yeast growth and reduce viability, moreover, they have a synergistic effect when combined (Ingram and Buttke 1984;Seward et al 1996). Damage to cell membranes (Ingram and Buttke 1984), reduced uptake of glucose and amino acids (Lester 1965), and reduction in respiratory capacity are some mechanisms involved in this inhibition phenomena. In situ product removal (ISPR) has been proven to be a useful approach for circumventing the problem of product inhibition .…”
Section: Introductionmentioning
confidence: 99%
“…The deprivation of the cell activity was possibly caused by the damages to cell membrane since aromatic alcohol tends to raise the membrane fluidity as its target site. [23] To further investigate the product inhibition, the kinetic study for biotransformation of L-Phe 1 to 2-PE 6 with E. coli (RE) cells (5 g cdw/L) was conducted in the presence of 0-3 mM 2-PE 6. The reaction was performed in KP buffer (100 mM, pH 8.0) and n-hexadecane (1 : 1; v/v) at 30°C for 15 mins.…”
Section: Cascade Biotransformation Of L-phe 1 To 2-pe 6 and Product Imentioning
confidence: 99%